2009
DOI: 10.5194/acpd-9-15827-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneous freezing of droplets with immersed mineral dust particles – measurements and parameterization

Abstract: Abstract. During the measurement campaign FROST (FReezing Of duST), LACIS (Leipzig Aerosol Cloud Interaction Simulator) was used to investigate the immersion freezing behavior of coated and uncoated Arizona Test Dust (ATD) particles with a mobility diameter of 300 nm. Particles were coated with succinic acid (C4H6O4), sulfuric acid (H2SO4, two different coating conditions), and ammonium sulfate ((NH4)2SO4). Ice fractions at temperatures between 233.15 K and 240.65 K were determined for all types of particles a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 39 publications
7
46
0
Order By: Relevance
“…Thereby, the mineralogical composition of soil particles acting as CCN respective IN, the particles shape and surface structure, and their microphysical properties are relevant for its successful action in cloud formation processes. The role of mineral dust particles in cloud formation processes is observed during several measurement campaigns (e.g., [138]) and confirmed by laboratory studies (e.g., [139]). Modeling studies implementing observed dust-cloud interaction processes provide insights into regional and global implications as well as they enable the community to assess the relevance of dust-cloud interactions for the atmospheric energy budget, the hydrological cycle and thus the Earth climate.…”
Section: Cloudssupporting
confidence: 57%
“…Thereby, the mineralogical composition of soil particles acting as CCN respective IN, the particles shape and surface structure, and their microphysical properties are relevant for its successful action in cloud formation processes. The role of mineral dust particles in cloud formation processes is observed during several measurement campaigns (e.g., [138]) and confirmed by laboratory studies (e.g., [139]). Modeling studies implementing observed dust-cloud interaction processes provide insights into regional and global implications as well as they enable the community to assess the relevance of dust-cloud interactions for the atmospheric energy budget, the hydrological cycle and thus the Earth climate.…”
Section: Cloudssupporting
confidence: 57%
“…Figure 3 shows an example of the image frame being filled with droplets and highlights the maximum number of droplets that could be analysed per experiment based on the optics used, a number that could be increased if needed by either generating smaller droplets, using lower-magnification optics, or by using a CCD camera with a wider field of view. The fraction of droplets frozen, f ice ( T ), by temperature T for a range of atmospherically relevant INP was calculated (Vali 1971 , 1994 ; Connolly et al 2009 ; Niedermeier et al 2010 ; Niemand et al 2012 ): where n ice ( T ) is the total number of frozen droplets at temperature T and n tot is the total number of droplets. In order to avoid contact freezing, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of stochastic fluctuations of the ice germ size in a supercooled droplet on the freezing temperature of the droplet is less clear and has been the subject of recent research [Vali, 2008]. Formulations on the basis of both singular hypotheses [e.g., Connolly et al, 2009] and stochastic hypotheses [e.g., Niedermeier et al, 2009] have been used to describe droplet freezing rates in recent studies.…”
mentioning
confidence: 99%